‫دور‬‫النشاط‬ ‫البدني‬ ‫المكيف‬ ‫في‬ ‫تحسين‬ ‫بعض‬ ‫مهارات‬‫االتصال‬ ‫اللفظي‬ ‫وغير‬ ‫اللفظي‬ ‫لدى‬ ‫المصابين‬‫بتأخر‬ ‫النطق‬ - ‫حمو‬ ‫علي‬ ‫أ‬ ‫م‬‫حمد‬; أسامة مرزوقي (My University, 2025)
‫لدى‬ ‫اللفظي‬ ‫وغير‬ ‫اللفظي‬ ‫االتصال‬ ‫مهارات‬ ‫بعض‬ ‫تحسين‬ ‫في‬ ‫المكيف‬ ‫البدني‬ ‫النشاط‬ ‫دور‬ ‫على‬ ‫التعرف‬ ‫إلى‬ ‫الدراسة‬ ‫تهدف‬ ‫التربية‬ ‫مجاالت‬ ‫في‬ ‫ومختص‬ ‫مربي‬ 20 ‫من‬ ‫متكونة‬ ‫عينة‬ ‫على‬ ‫الوصفي‬ ‫منهج‬ ‫استخدمنا‬ ‫الغرض‬ ‫ولهذا‬ ،‫النطق‬ ‫بتأخر‬ ‫المصابين‬ ‫العيد‬ ‫حكومي‬ ‫الشهيد‬ ً ‫ذهنيا‬ ‫المعاقين‬ ‫لألطفال‬ ‫البيداغوجي‬ ‫النفسي‬ ‫المركز‬ ‫من‬ ‫الحركي‬ ‫النفسي‬ ‫أهيل‬‫والت‬ ،‫والتخاطب‬ ‫النطق‬ ،‫الخاصة‬ ‫تم‬ 2024/2025 ‫الدراسي‬ ‫للموسم‬ ‫باألغواط‬ ‫بسباس‬ ‫قدور‬ 02 ً ‫ذهنيا‬ ‫المعاقين‬ ‫لألطفال‬ ‫البيداغوجي‬ ‫النفسي‬ ‫والمركز‬ ‫بتيميمون‬ :‫النتائج‬ ‫إلى‬ ‫التوصل‬ ‫تم‬ ‫إحصائيا‬ ‫ومعالجتها‬ ‫النتائج‬ ‫جمع‬ ‫بعد‬ ،‫ستبيان‬‫اال‬ ‫استمارة‬ ‫استخدمنا‬ ‫البيانات‬ ‫لجمع‬ ،‫عشوائي‬ ‫بشكل‬ ‫اختيارها‬ ‫األطفال‬ ‫لدى‬ ‫اللفظي‬ ‫وغير‬ ‫اللفظي‬ ‫االتصال‬ ‫مهارات‬ ‫تنمية‬ ‫على‬ ‫واضح‬ ‫إيجابي‬ ‫تأثير‬ ‫لها‬ ‫المكيف‬ ‫الرياضي‬ ‫النشاط‬ ‫ممارسة‬ ‫إن‬ ‫العالج‬ ‫برامج‬ ‫ضمن‬ ‫الموجهة‬ ‫الرياضية‬ ‫األنشطة‬ ‫إدماج‬ ‫ضرورة‬‫ب‬ ‫الدراسة‬ ‫أوصت‬ ‫األساس‬ ‫هذا‬ ‫وعلى‬ .‫النطق‬ ‫بتأخر‬ ‫المصابين‬Adapted sports activity / Verbal and nonverbal communication skills / Speech delay
‫دراسة‬‫ميدانية‬ ‫على‬ ‫على‬ ‫مستوى‬ ‫المركز‬ ‫النفسي‬ ‫البيداغوجي‬ ‫لألطفال‬ ‫المعاقين‬ ‫ذهنيا‬ ‫ً‬ ‫الشهيد‬ ‫حكومي‬ ‫العيد‬ ‫بتيميمون‬
The Object of the study aims to identify The role of adapted physical activity in improving some verbal and nonverbal communication skills in people with delayed speech, for this purpose, we used the method Descriptive On a sample composed of 20 educators and specialists in the fields of special education, speech and communication, and psychomotor rehabilitation from the Psycho- Pedagogical Center for Mentally Handicapped Children, Shahid Hokomi El Eid, in Timimoun and the Psycho-Pedagogical Center for Mentally Handicapped Children, 02 Kadour Besbas, in Laghouat, for the 2024/2025 academic year Chosen as random, and for data collection, we used a tool Questionnaire .After collecting the results and having treated them statistically, we conclude Adapted physical activity has a clear positive effect on the development of verbal and nonverbal communication skills in children with speech delay. On this basis, the study recommended the need to integrate targeted sports activities into language therapy and rehabilitation programs for children with speech delays